2016
DOI: 10.1080/00016489.2016.1247984
|View full text |Cite
|
Sign up to set email alerts
|

A recurrence model for laryngeal cancer based on SVM and gene function clustering

Abstract: A total of 725 DEGs were identified from the training set. A total of 4126 gene pairs showed significant correlations in non-recurred LC only, corresponding to 533 genes. A total of 7235 gene pairs showed significant correlations in recurred LC only, corresponding to 608 genes. Besides, 1694 gene pairs showed significant correlations in both non-recurred and recurred LC, corresponding to 322 genes. Functional enrichment analysis was performed for the three groups of DEGs. Seven overlapping biological functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Previous findings have shown that in aortic tissue, destruction of MYH11 can lead to vascular smooth muscle cell loss, disorganization and hyperplasia, which is one of the mechanisms leading to thoracic aortic aneurysms and dissections (6,7). In previous years, studies have indicated that mutations of the MYH11 gene are also associated with various types of cancer, including colorectal (8,9), bladder (10), laryngeal (11) and head and neck cancer (12). This may be due to the role of MYH11 role in cell migration, interaction with cell adhesion proteins and tumor suppression (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous findings have shown that in aortic tissue, destruction of MYH11 can lead to vascular smooth muscle cell loss, disorganization and hyperplasia, which is one of the mechanisms leading to thoracic aortic aneurysms and dissections (6,7). In previous years, studies have indicated that mutations of the MYH11 gene are also associated with various types of cancer, including colorectal (8,9), bladder (10), laryngeal (11) and head and neck cancer (12). This may be due to the role of MYH11 role in cell migration, interaction with cell adhesion proteins and tumor suppression (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more researches have been conducted to verify the accuracy of tumor biomarker prediction based on SVM classifiers [12,24,25]. In this study, we identified five important biological functions through RFE which included GO: 0007242~intracellular signaling cascade, GO:0006140~regulation of nucleotide metabolic process, hsa04080: Neuroactive ligand-receptor interaction, hsa04120: Ubiquitin mediated proteolysis, hsa04142: Lysosome.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have revealed that MYH11 is a biomarker of BLCA (15,17), which is consistent with our conclusion. Additionally, the expression level of MYH11 has been reported to be dysregulated in colorectal cancer (33,34), lung cancer (35), laryngeal cancer (36) and acute myeloid leukemia (37). Based on these researches above mentioned, we speculate that myosin-dependent contractile activity in nonmuscle cells may be participated in cell adhesion and migration to promote tumor invasion.…”
Section: Discussionmentioning
confidence: 84%